If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -5 = 7 + 4X Reorder the terms: -5 + X = 7 + 4X Solving -5 + X = 7 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. -5 + X + -4X = 7 + 4X + -4X Combine like terms: X + -4X = -3X -5 + -3X = 7 + 4X + -4X Combine like terms: 4X + -4X = 0 -5 + -3X = 7 + 0 -5 + -3X = 7 Add '5' to each side of the equation. -5 + 5 + -3X = 7 + 5 Combine like terms: -5 + 5 = 0 0 + -3X = 7 + 5 -3X = 7 + 5 Combine like terms: 7 + 5 = 12 -3X = 12 Divide each side by '-3'. X = -4 Simplifying X = -4
| p/7=12/5 | | [10x-5]+4=8 | | 6(b-6)=8(b+6) | | h=-16t+104t | | 1-2Inx=0 | | 3/t=8/3 | | 6x-1/y=5 | | 7/11=5/n | | 7/t=11/7 | | 7t=11/7 | | -10+2w=-6 | | -11y+5y=14 | | 6/y=3/7 | | 3+77x=44x+6 | | 32-15x=-18+9 | | 11/10=y/12 | | 4k+33=1-3k | | 8g-5w=4 | | a/10=4/9 | | 4a^9+5=8 | | 7+5y-4=6y+6-2y | | 3*(3-x)=5x+27 | | 7x-42=2x+12 | | 4x+10=-35-5 | | 1j^5-7=12 | | X-10=-4X | | 5b^2-36b=32 | | a+f=10 | | 1k+q=8 | | 3+10x=-6+x | | 2x-4=5x-12 | | 47x+(-13y)=0 |